Superstar Fitness' Default Dispute for Negligence in Contract Agreement - Gani, Maria Minerva; Lauren, Callista; Maukar, Michelle Regine (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The dispute case between PT Cipta Usaha Amerta Nusantara and its creditors reveals the complexity of default in the implementation of the interior construction service contract. This research aims to analyze (1) the legal position of contract agreements in bankruptcy cases, (2) the application of the concept of debt as a form of default in treaty law, and (3) the legal possibilities that creditors have to recover their rights in the form of compensation, interest, or costs. The research method used is normative legal method with prescriptive and hermeneutic approaches. The decision of the Commercial Court at the Central Jakarta District Court shows that the bankruptcy petition cannot be granted because the minimum requirement of two legitimate creditors is not met. Nevertheless, the respondent's negligence in fulfilling its payment obligations towards the applicant and other parties, both employees and customers, showed a clear default. This research also reveals that creditors have a strong legal basis to demand the fulfillment of rights through default lawsuits and bankruptcy if the formal requirements are met. Therefore, more careful contract management and an adequate company financial monitoring system are required to avoid widespread losses for the parties involved.